Evidence of Alcohol-Related Efficiency Deficits in an Episodic Learning Task. - Nixon, Sara J.; Bowlby, David (Alcoholism: Clinical & Experimental Research, 1996)
Using a component processes model, the current study examined the cognitive processes of alcoholic and community control subjects engaged in the acquisition of new context-bound (e.g., episodic) information. Of particular interest was whether alcoholics were inferior to controls in the efficiency with which information was acquired and whether there was a gender × group interaction in cognitive efficiency. Alcoholic ( n= 16 females; n= 22 males) and community control ( n= 21 females; n= 21 males) subjects participated in a serial learning task that consisted of three 12-item word lists. Standard administration protocols for serial learning tasks were used. On efficiency measures, there were significant differences between groups [ F(1,75) = 8.51, p= 0.005] and sexes [ F(1,75) = 4.05, p= 0.048]. There was also a group × sex interaction [ F(1,75) = 7.73, p= 0.007]. Duncan multiple-range comparisons revealed alcoholic females to be significantly inferior to control females, but equivalent to male controls and alcoholics. These data are consistent with other studies revealing the sensitivity of cognitive efficiency to alcohol-related effects and extend previous findings to tasks involving episodic learning tasks.